2017
DOI: 10.1177/2050312117735774
|View full text |Cite
|
Sign up to set email alerts
|

A review of orexin’s unprecedented potential as a novel, highly-specific treatment for various localized and metastatic cancers

Abstract: A systematic review was conducted to categorize the types of cancerous tissues that express orexin receptors and also to examine the effect of in vitro administration of orexin A or B to corresponding cell samples. Comprehensive literature analyses of primary experimental studies were performed. The results of the review included an increased frequency of orexin receptor expression in many colon and prostate cancer tissues and an upward trend of pro-apoptotic activity in these aggressive cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Like the peripheral biological role of orexins that remains still under discussion ( 86 ), OXR expression and orexins actions in cancer have been poorly documented ( 87 ). Several lines of evidence indicated that OX1R/OX2R were expressed in various cancer cells, but their actions depended on the cancer types.…”
Section: Other Cancersmentioning
confidence: 99%
“…Like the peripheral biological role of orexins that remains still under discussion ( 86 ), OXR expression and orexins actions in cancer have been poorly documented ( 87 ). Several lines of evidence indicated that OX1R/OX2R were expressed in various cancer cells, but their actions depended on the cancer types.…”
Section: Other Cancersmentioning
confidence: 99%
“…In recent years, a series of studies have been conducted on the role of orexins not only in the field of sleep disorders but also in oncology, discovering that modulation of the orexin signaling may also unexpectedly play a therapeutic role in the treatment of some types of cancer [ 120 , 121 ]. One study demonstrated that OXA stimulates neovascularization [ 122 ].…”
Section: Orexin Cancer and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Следует отметить, что большинство исследователей изучали эффект орексина А, но не орексина B. Возможно, это вызвано тем, что орексин А более «универсален»: он имеет одинаковое сродство к обоим рецепторам орексина -OX1R и OX2R, в то время как орексин B избирательно связывается с OX2R [19].…”
Section: Figure 2 Classical and Alternative Signaling Of Orexin Receptorsunclassified
“…Аминокислотная гомология OX1R и OX2R составляет 64%. OX1R имеет высокое сродство к орексину А, в то время как OX2R неселективен по отношению к обоим типам орексинов [19]. Хотя рецепторы орексинов имеют некоторые структурные сходства с рецепторами других нейропептидов, например нейропептида Y и меланокортина, они не демонстрируют связывания с нейропептидом Y, меланокортином и секретином, что еще раз свидетельствует о высокой избирательности рецепторов по отношению к лиганду [61].…”
Section: Introductionunclassified